Navigating Religious Pluralism in Nigerian Public Administration: A Mixed-Methods Inquiry into Governance, Identity, and Policy - Ezeudu, Tochukwu Simon; Saadu, Yahaya (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2025)
Religion is deeply embedded in Nigeria’s social and political life, and it routinely shapes governance by influencing policy-making, administrative practice, and public trust. In a religiously plural context where the boundaries of state neutrality are frequently contested, religious influence can be ambivalent: it may support ethical public service while also intensifying perceptions of partiality and generating tension within institutions. Drawing on Peter L. Berger’s theory of religious pluralism, this article examines how religious beliefs, identities, and religious actors affect public administration in Nigeria. Employing a mixed-methods design, the study integrates qualitative evidence from semi-structured interviews and focus group discussions with quantitative analysis of survey data from public officials across three religiously diverse regions. The findings indicate that religious affiliation significantly shapes perceptions of policy initiatives and levels of trust in government institutions, whilst religious leaders often function as intermediaries or gatekeepers within policy processes. Trust in government is positively associated with religious identity, occupational status within the public sector, and age, whereas gender shows limited explanatory power, alongside persistent concerns regarding religious favouritism in administrative procedures. This study contributes an empirically grounded account of religion’s procedural effects on Nigerian public administration and advances Berger’s pluralism as an applied analytical lens that links claims of ethical governance to observable patterns of trust and perceived bias, with implications for inclusive policy frameworks, interfaith engagement, and professional ethics training for public officials.